Comparative Evaluation of Platelet-Rich Plasma Versus Normal Saline as Intraoperative Holding Solutions in FUE Hair Transplantation - Kamal, Neel; Kasliwal, Rishabh; Rastogi, Komal; Phogat, Sonika; Chaudhary, Julee; Joya, Vahid Ali; Verma, Ravi Kumar (Journal of Neonatal Surgery, 2025)
Background: Intraoperative graft survival remains a pivotal determinant of successful outcomes in Follicular Unit Extraction (FUE) hair transplantation. Conventionally, Normal Saline (NS) has been used to preserve grafts during the ex vivo interval; however, it lacks bioactive or regenerative properties. Platelet-Rich Plasma (PRP), an autologous concentrate rich in growth factors such as PDGF, VEGF, and TGF-β, may enhance follicular viability by modulating inflammation, oxidative stress, and ischemia-induced apoptosis. The Aim of the work: This study aims to prospectively evaluate and compare the clinical and histological outcomes of Platelet-Rich Plasma versus Normal Saline as intraoperative holding solutions during FUE hair transplantation. Patients and Methods: Ten male patients diagnosed with Androgenetic Alopecia (AGA) Grades II–VI were randomly assigned into two equal groups: Group A (PRP) and Group B (NS). FUE was performed on all patients, and grafts were preserved in their respective solutions at 4°C before implantation. Evaluation parameters included follicular survival rate, hair density (FU/cm²), shaft length and thickness, postoperative complications, and patient satisfaction (VAS). Follow-up was conducted at 1, 3, 6, and 12 months. Histopathological comparisons were made using H&E-stained biopsies from recipient areas [3], [4]. Results: Group A (PRP) demonstrated a significantly higher graft survival rate (84% vs. 73%, p < 0.01), greater mean hair shaft thickness (58.6 µm vs. 49.2 µm), and improved density (71.2 FU/cm² vs. 66.0 FU/cm²) compared to Group B. VAS scores were also higher in Group A (8.8 vs. 7.4, p < 0.01). Histological evaluation confirmed better preservation of outer root sheath, sebaceous glands, and arrector pili muscle in PRP-treated grafts [5], [6]. Conclusion: PRP provides a bioactive microenvironment that significantly enhances graft survival, hair shaft maturation, and overall aesthetic outcomes compared to Normal Saline. It offers a safe, cost-effective, and easily implementable intraoperative enhancement for improving FUE hair transplant results.